1994
DOI: 10.1302/0301-620x.76b1.8300651
|View full text |Cite
|
Sign up to set email alerts
|

Ligamentotaxis with an internal spinal fixator for thoracolumbar fractures

Abstract: We assessed narrowing of the spinal canal in 39 burst fractures and fracture-dislocations of thoracolumbar vertebrae treated by the AO Internal Spinal Fixator, using CT preoperatively and at various stages postoperatively. Computer-aided planimetry was used to measure the narrowing, and its restoration shortly after instrumentation, or at 15 months. The mean initial reduction of canal area was to 63.7% +/- 18.8% of normal; this was restored to a mean of 95.4% +/- 21.2% of normal when measured either soon after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1
11

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 6 publications
0
39
1
11
Order By: Relevance
“…This approach provides better exposure of the fractured vertebrae, enabling a more thorough decompression [10]. In contrast, the posterior approach can only support indirect decompression [31]. Therefore, good canal remodeling after canal encroachment occurred in the anterior approach group just as all the included studies concerning this parameter.…”
Section: Discussionmentioning
confidence: 96%
“…This approach provides better exposure of the fractured vertebrae, enabling a more thorough decompression [10]. In contrast, the posterior approach can only support indirect decompression [31]. Therefore, good canal remodeling after canal encroachment occurred in the anterior approach group just as all the included studies concerning this parameter.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have shown that posterior indirect reduction corrects the canal compromise adequately due to a combination of distraction ligamentotaxis and forced hyperextension [26,34]. The canal compromise remaining postoperatively may further decrease to near normal over time due to the pulsations of the thecal sac [5,23].…”
Section: Spinal Canal Compromisementioning
confidence: 99%
“…Originally, ligamentotaxis was defined as a method for indirect reduction of a fracture by the application of a strong distraction force, which is transmitted through intact ligaments and capsules 1) . This phenomenon is applied mainly to the thoracolumbar burst fracture.…”
Section: Discussionmentioning
confidence: 99%
“…However, a prerequisite for ligamentotaxis is an intact PLL and attachment of the retropulsed fragments to the ligament 2) . In addition, the effect of ligamentotaxis is weak below the L3 level for anatomical reason 1) . Therefore, the A ligamentotatic effect on disc herniation may be applied to the contained disc herniation above the L3/4 level.…”
Section: Discussionmentioning
confidence: 99%